CERAI GUGAT PERSPEKTIF PERUNDANG-UNDANGAN DI INDONESIA (STUDI KASUS DI PENGADILAN AGAMA KELAS 1B WATAMPONE PADA TAHUN 2010-2012) - Darliana Darliana (Al-Risalah: Jurnal Hukum Keluarga Islam (Ahwal Al-Syakhsiyah), 2021)
Abstract The results show that the divorce to sue in the Religious Class 1B Watampone from year to year has increased significantly, the events of divorce sue greater in number than the divorce on the grounds that the wife is more aware of their rights and obligations in marriage. Factors that lead to divorce contested in the Religious are factors moral, Hurting, child marriage, dispute continuously, biological defect and no harmony, these factors are supported by a state of "inability" and "unwillingness" in running rights and obligations in marriage resulting in a violation of the party. Divorced jerknegative impact for both parties and its offspring. These impacts include the psychological impact on the children and the wife because the resulting Psychological and mental, social impact on the husband and wife because the predicate status of widows and widowers, economically affect the financial borne wife during the marriage the husband. While the solution regarding custody of the child given to her for a child is not mumayyiz and joint property during the marriage should be halved fair and equitable manner.